Venous Flow Profiles on Perfusion CT are Associated with Futile Recanalization After Thrombectomy - Su M; Chen Z; Chen X; Huang J; Li Z; Zhou Y; Xu G (Neuropsychiatric Disease and Treatment, 2022)
Mouxiao Su,1,2 Zhonglun Chen,2 Xinyue Chen,3 Jiaxing Huang,4 Zhaokun Li,2 Ying Zhou,4 Gelin Xu1,5 1The First School of Clinical Medicine, Southern Medical University, Guangzhou, 510000, People’s Republic of China; 2Department of Neurology, School of Medicine, Mianyang Central Hospital, University of Electronic Science and Technology of China, Mianyang, 621000, People’s Republic of China; 3CT Collaboration, Siemens Healthineers, Chengdu, 610000, People’s Republic of China; 4Department of Radiology, School of Medicine, Mianyang Central Hospital, University of Electronic Science and Technology of China, Mianyang, 621000, People’s Republic of China; 5Department of Neurology, Jinling Hospital, Medical School of Nanjing University, Nanjing, 210002, People’s Republic of ChinaCorrespondence: Gelin Xu, The First School of Clinical Medicine, Southern Medical University, Guangzhou, 510000, People’s Republic of China, Tel +86 18951919349, Email gelinxu@nju.edu.cnBackground and Purpose: Robust venous outflow (VO) reflects favourable tissue reperfusion in acute ischaemic stroke (AIS) patients with large vessel occlusion (LVO). We aimed to investigate the association of the venous outflow profile on computed tomographic perfusion (CTP) and futile recanalization in anterior circulation AIS patients with LVO after thrombectomy.Methods: This was a retrospective study of consecutive AIS patients due to anterior circulation LVO who underwent CTP before thrombectomy. Patients who achieved successful recanalization defined as a modified Thrombolysis in Cerebral Infarction (mTICI) score of 2b or 3 after thrombectomy were included. Based on the venous time–intensity curve of CTP, the peak time of venous outflow (PTV), total venous outflow time (TVT), and difference value of arteriovenous peak time (D-value) were recorded. A modified mRS score of 3– 6 at 3 months was regarded as futile recanalization (FR). Logistic regression analysis was applied to assess risk factors for FR. We used receiver operating characteristic curves (ROCs) to evaluate the predictive value of venous outflow time parameters based on VO for FR.Results: Eighty patients were included; 35 (43.8%) achieved good functional outcomes, and 45 (56.3%) had unfavourable functional outcomes, that is, FR. Adjusting confounding factors, binary stepwise logistic regression analysis showed that delayed PTV was independently associated with FR (odds ratio, 1.374 [95% CI, 1.093– 1.726], P = 0.007). ROCs indicated that PTV effectively predicted unfavourable outcomes at 3 months (area under the curve (AUC) = 0.729, p< 0.001). The combined model was a powerful predictor of FR with an AUC of 0.824 and a cut-off value of 0.631 (p< 0.001).Conclusion: Delayed PTV is independently related to FR in anterior circulation AIS patients with LVO achieving successful recanalization after thrombectomy. Our results highlight that the time of VO may be a potential marker for FR.Keywords: time intensity curve, computed tomographic perfusion, futile recanalization, thrombectomy